Bioaerosol sampling: sampling mechanisms, bioefficiency and field studies. Issue 3 (July 2016) - Haig, C.W.; Mackay, W.G.; Walker, J.T.; Williams, C.
Summary: Investigations into the suspected airborne transmission of pathogens in healthcare environments have posed a challenge to researchers for more than a century. With each pathogen demonstrating a unique response to environmental conditions and the mechanical stresses it experiences, the choice of sampling device is not obvious. Our aim was to review bioaerosol sampling, sampling equipment, and methodology. A comprehensive literature search was performed, using electronic databases to retrieve English language papers on bioaerosol sampling. The review describes the mechanisms of popular bioaerosol sampling devices such as impingers, cyclones, impactors, and filters, explaining both their strengths and weaknesses, and the consequences for microbial bioefficiency. Numerous successful studies are described that point to best practice in bioaerosol sampling, from the use of small personal samplers to monitor workers' pathogen exposure through to large static samplers collecting airborne microbes in various healthcare settings. Of primary importance is the requirement that studies should commence by determining the bioefficiency of the chosen sampler and the pathogen under investigation within laboratory conditions. From such foundations, sampling for bioaerosol material in the complexity of the field holds greater certainty of successful capture of low-concentration airborne pathogens. From the laboratory to use in the field, this review enables the investigator to make informed decisions about the choice of bioaerosol sampler and its application.